2014
DOI: 10.1002/ijc.28815
|View full text |Cite
|
Sign up to set email alerts
|

Association study of a functional copy number variation in the WWOX gene with risk of gliomas among Chinese people

Abstract: Gliomas represents more than 80% of all malignant brain tumors. However, the etiology still remains largely unknown. Human WW domain-containing oxidoreductase (WWOX), which is located at 16q23.1-16q23.2, the common fragile site 16D (FRA16D), an area with a high frequency of gene deletions or chromosomal alterations, has been identified as a tumor suppressor gene in multiple cancers. In current study, we analyzed the WWOX deletion (CNV-67048) in a large, case-control study of 3,622 adult Chinese people (includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 24 publications
1
28
0
Order By: Relevance
“…It was reported that germline variant originally identified as CNV‐67048 of 13.3 Kbp in size mapping to chr16:76929120‐76942453 assembly NCBI36/hg18 (chr16:78337722‐78351055 in GRCh38/hg38) has been linked to the risk of lung cancer, gliomas, ovarian cancer, and also to chronic obstructive pulmonary disease . It must be noted that CNV‐67048 does not correspond to any currently existent nomenclature, however, based on its chromosomal coordinates is the same as esv22307 originally described as a complex variant for both copy number losses but also gains in humans and not just losses as reported in the aforementioned previous studies . It is worth noting that esv22307 lies within the previously described hot spot for germline duplications and deletions within intron 5 of WWOX (Figure ).…”
Section: Wwox Is a Hot Spot For Germline Cnv Polymorphismsmentioning
confidence: 99%
“…It was reported that germline variant originally identified as CNV‐67048 of 13.3 Kbp in size mapping to chr16:76929120‐76942453 assembly NCBI36/hg18 (chr16:78337722‐78351055 in GRCh38/hg38) has been linked to the risk of lung cancer, gliomas, ovarian cancer, and also to chronic obstructive pulmonary disease . It must be noted that CNV‐67048 does not correspond to any currently existent nomenclature, however, based on its chromosomal coordinates is the same as esv22307 originally described as a complex variant for both copy number losses but also gains in humans and not just losses as reported in the aforementioned previous studies . It is worth noting that esv22307 lies within the previously described hot spot for germline duplications and deletions within intron 5 of WWOX (Figure ).…”
Section: Wwox Is a Hot Spot For Germline Cnv Polymorphismsmentioning
confidence: 99%
“…The copy number of a CNV located at 16q23.1-16q23.2 including WWOX is associated with susceptibility to glioma; the decrease in the copy number of the CNV increases a possibility of glioma development [44]. The odds ratio for glioma development is reported 1.21 for 1-copy loss and 1.94 for 2-copy loss.…”
Section: Gliomamentioning
confidence: 99%
“…8 Recently, a similar association has been found between the CNV-67048 genetic variant and risk of gliomas. 9 Characteristics of the WWOX protein sequence…”
Section: Introductionmentioning
confidence: 99%